2021
DOI: 10.1590/1678-7757-2020-0678
|View full text |Cite
|
Sign up to set email alerts
|

Dental workers in front-line of COVID-19: an in silico evaluation targeting their prevention

Abstract: Dental workers in front-line of COVID-19: an in silico evaluation targeting their prevention SARS-CoV-2 has high human-human transmission rate. The aerosols and saliva droplets are the main contamination source. Thus, it is crucial to point out that dental practitioners become a high-risk group of contagion by SARS-CoV-2. Based on this, protocols have been recommended to avoid cross-contamination during dental care; however, appropriate evidence has not yet been established. Objective: Our study sought to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…CHX is a simple and safe addition to current COVID-19 prevention guidelines and may play an important role in reducing the spread of disease [4,14] . The overall results suggested that chlorhexidine is the most suitable active compound to reduce the salivary load of SARS-CoV-2 due to its better binding energy [15] . Most studies demonstrated that CHX has positive virucidal efficacy against HSV-1 and InfluA strains [16] .…”
Section: Chlorhexidinementioning
confidence: 92%
“…CHX is a simple and safe addition to current COVID-19 prevention guidelines and may play an important role in reducing the spread of disease [4,14] . The overall results suggested that chlorhexidine is the most suitable active compound to reduce the salivary load of SARS-CoV-2 due to its better binding energy [15] . Most studies demonstrated that CHX has positive virucidal efficacy against HSV-1 and InfluA strains [16] .…”
Section: Chlorhexidinementioning
confidence: 92%
“…One study attributed the antiviral effects of povidone-iodine to its direct cytotoxicity to infected host cells [ 41 ] while another study suggested that povidone-iodine could destabilize the lipid envelope, lyse spike proteins and oxidize the nucleic acid of virus particles [ 42 ]. These actions are less likely to be mediated by binding of povidone-iodine to specific viral targets as data from in silico studies suggest poor affinity of povidone-iodine for SARS-CoV-2 proteins [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the recent computational drug modeling study 19 showed promising results regarding the increased binding affinity of CHX with SARS-CoV-2 proteins, in silico-based compound-protein physical interactions might not yield the same results in realtime clinical settings.…”
mentioning
confidence: 99%